The callenges and adaptation in career for the dwarfs: a literature review - Zainudin, Zaida Nor; Abdul Rasid, Nur Syuhada; Mohamad Yusop, Yusni; Wan Othman, Wan Norhayati; Lee, Wei Rong (Human Resource Management Academic Research Society, 2021)
The dwarfs are the disabled group that is less discussed in Malaysia. Same with other disabilities, the dwarfs had facing their own challenges. Challenges such as their physical condition, the environment, and society. The research that done in this area is very limited. Therefore, this systematic literature review objectives are to identify the challenges faced by the dwarfs and to see how the dwarfs adapt with the environment especially in career. Keywords of dwarfs and job applied in searching of articles. The inclusion and exclusion criterion were limited to year 2013 to 2018. Specific subject area was selected in screening process. A total of 12 articles were identified and used to explain the objectives of this study. The results show that the dwarfs have issues in social, environmental adjustments and medicine bound. These issues influence their career achievement and career advancement. The implication based on the help of government, self-identified and career stability on dwarfs were discussed in this study.